Multiple HBV transfusion transmissions from undetected occult infections: revising the minimal infectious dose - Candotti, Daniel; Assennato, Sonny Michael; Laperche, Syria; Allain, Jean-Pierre; Levicnik-Stezinar, Snezna (Gut, 2019)
ObjectiveHBV infection by blood components is currently prevented in most developed countries by combining sensitive HBV surface antigen (HBsAg) assays, nucleic acid testing (NAT) and in a few of them antibodies against the HBV core antigen (anti-HBc) screening. HBV transmissions by blood components from three repeat donors tested negative for HBsAg and HBV DNA with a highly sensitive screening test (limit of detection (LOD): 3.4 IU/mL) were investigated.Design30 of the 47 recipients of components produced from these three donors were examined. Transfusion transmission was confirmed by phylogenetic analysis of viral sequences obtained from recipients and donors following viral particle concentration.Results9 of 31 (29%) recipients were infected: 7 infections were related to 200 mL of fresh frozen plasma and 2 infections to red blood cells containing 20 mL plasma. Transfusion transmission was confirmed by >99% identity of donor/recipient sequences in five cases, probable in three and possible in one. HBV active infection remained unsuspected for 24–57 months in three recipients. Five non-infected recipients carried anti-HBs when transfused. Six patients transfused with platelet concentrates treated with a pathogen reduction method were not infected. These data enabled to revise previous estimate of the minimal infectious dose from approximately 100 to 16 copies (or 3 IU) of HBV DNA.ConclusionsHBV transfusion transmission from occult HBV infection carrying extremely low viral loads is related to plasma volume transfused and possibly prevented by anti-HBs. HBV blood safety could be further improved by either anti-HBc screening, HBV DNA NAT with a LOD of 0.8 copies/mL (0.15 IU/mL) or pathogen reduction of blood components.